7th International Symposium on Superalloy 718 and Derivatives (2010) 2010
DOI: 10.7449/2010/superalloys_2010_271_280
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced Cast/Wrought Technology for GH720Li Alloy Disk from Fine Grain Ingot

et al.

Abstract: The cast & wrought (C&W) route is one of the earliest production techniques and still commonly used in the overall production of turbine components due to its low cost and processing benefits. However, the C&W route can not be applied to some modern disk alloys that contain high volume fraction of γ′ phase and refractory alloying elements. Therefore, the latest Ni-base disk alloys such as RR1000, Rene 95 and ME3 are produced by powder metallurgy processing routes. However, the requirement of clean powder and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Problems such as short working temperature range and low thermal conductivity may cause cracks or non-uniform structures during hot working. Previous research indicated that hot ductility has intimately relationship with deformation parameters [2], it is necessary to investigate the effects of parameters on deformation rules.…”
Section: Introductionmentioning
confidence: 99%
“…Problems such as short working temperature range and low thermal conductivity may cause cracks or non-uniform structures during hot working. Previous research indicated that hot ductility has intimately relationship with deformation parameters [2], it is necessary to investigate the effects of parameters on deformation rules.…”
Section: Introductionmentioning
confidence: 99%